2008
DOI: 10.1111/j.1744-7348.2008.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Humic acids crossinteractions with root and organic acids

Abstract: The apparent high molecular mass of humic acids (HAs) hardly seems compatible with their direct effects in plant physiology. However, previous evidence has indicated that HAs are non-covalent associations of relatively small molecules, which can be broken down by the action of organic acids. The aim of this work was to evaluate the effects of organic acids on the structure of HAs by spectroscopy and on their bioactivity by following the responses of maize root growth. Changes in the exudation of organic acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
90
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 50 publications
11
90
0
8
Order By: Relevance
“…Em solução, os AH podem liberar parte de seus componentes com a adição de pequenas quantidades de ácidos orgânicos (Piccolo et al, 1999;Cozzolino et al, 2001) tais como os exsudados pelas raízes. Além disso, Canellas et al (2008b) …”
Section: Resultsunclassified
“…Em solução, os AH podem liberar parte de seus componentes com a adição de pequenas quantidades de ácidos orgânicos (Piccolo et al, 1999;Cozzolino et al, 2001) tais como os exsudados pelas raízes. Além disso, Canellas et al (2008b) …”
Section: Resultsunclassified
“…Se, por um lado, a alteração da propriedade de permeabilidade seletiva da plasmalema em tese pode aumentar a entrada de íons, por outro pode favorecer também a saída, uma vez que a ação surfactante não preserva a seletividade das membranas (Nardi et al, 2002). Canellas et al (2008) verificaram que plântulas de milho, tratadas com AHv, modificam o seu perfil de exsudação radicular de ácidos orgânicos, aumentando, significativamente, a extrusão de ácido cítrico e oxálico. Em contato com o ambiente acidificado da rizosfera, as partículas supraestruturais dos ácidos húmicos podem se fragmentar e gerar subunidades potencialmente capazes de alterar o metabolismo celular, por meio da ativação de H + -ATPases da membrana plasmática de células de raiz (Piccolo, 2001;Façanha et al, 2002;Canellas et al, 2006).…”
Section: Discussionunclassified
“…According to Canellas et al (2008), humic substances have auxinic action. This is in agreement with Silva et al (2011), who reported, as the main physiological effect, the increase in root development, according to the species, plant age, source and concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Zandonadi & Busato (2012) and Zandonadi et al (2013; cite that humic substances can activate root and leaf development, increase in the absorption of nutrients and regulation of enzymes that govern plant metabolism, such as H + -ATPase and nitrate-reductase, and protons pumps are essential for the absorption of nutrients by plants. Canellas et al (2008) also described the occurrence of an auxinic action present in the humic substance.…”
Section: Introductionmentioning
confidence: 99%